ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS BANK PEMBIAYAAN RAKYAT SYARIAH INDONESIA - Tirta, Junita Puji Lestari; Rosyidah, Norma (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Measurement for the performance of a company is called Profitability. With the aim of measuring the company's ability to generate profits in a certain period. The purpose of this research is to analyze the factors that influence the profitability of Islamic BPRs. This type of research uses quantitative research with secondary data taken from the websites of the Financial Services Authority (OJK) and Bank Indonesia (BI). The data taken for the research is in the last three years from 2020-2022 in January-December. The methodology used in this study is the classical assumption test, determination test, F test and T test. The results of this study are the classic assumption test where normality and autocorrelation tests are significant. Meanwhile, in the classic assumption test, which tests the multicollinearity of the FDR and NPF variables, multicollinearity occurs. The autocorrelation test is also free from autocorrelation problems because the value of du < d < 4-du. The results of the determination test and F test are also significant. While the FDR and NPF T tests affect profitability. And the variables CAR, BOPO, Interest Rates, and Inflation have no effect on profitability Keywords: Profitability, interest rates, inflation